The leading practice of decision making in modern business systems : innovative technologies and perspectives of optimization - Popkova, Elena G.; Chesnokova, Alina V. (Emerald Publishing Limited, 2019)
Focusing on modern business systems from within the modern Russian context, this book examines how companies can become leading competitors globally within their industries through new decision making processes. Whilst current practices support the sustainability of a business system in terms of maintaining normal functionality and the prevention of crises, there is a need to consider the goals of leading organizations with larger business systems and greater resources. These goals can be more global in their focus and envisage the creation or strengthening of competitive advantages. Contributors of this book explore large scale industries specializing in hi-tech spheres of economy and instigate innovative activity in the face of high-levels of competition. Specific industries analyzed in this content include digital medicine, energy efficiency and car manufacturers. Using models of optimization and a range of real-world case studies, the book provides tools, technological analysis and techniques for practitioners to use within their own decision-making practices. For scholars researching business management, leadership and decision-making, this book also offers a useful insight into how optimized decision-making processes can be applied to the modern business system.
Introduction -- Part I. Generalization of the existing experience of decision making in modern business systems -- Chapter 1. The Russian model of decision making in modern business systems / Aleksei V. Bogoviz, Rustem T. Yuldashev, Margarita A. Menshikova, Olga V. Titova and Ekaterina S. Lebedeva -- Chapter 2. Current tendencies of transformation of the russian practice of decision making in business systems / Tatyana B. Leybert and Elvira A. Khalikova -- Chapter 3. Problems of decision making in business systems by the example of modern Russia's industry / Viktor P. Kuznetsov, Ekaterina P. Garina, Natalia S. Andryashina and Elena V. Romanovskaya -- Chapter 4. Barriers on the path of making of optimal decisions in business systems by the example of modern Russia / Larisa A. Ilyina, Yuliya A. Panteleeva, Dmitry L. Skipin and Alexandra N. Bystrova -- Chapter 5. Successful global experience of decision making in modern business systems / Tatyana Y. Anopchenko and Vladislav I. Ostrovskiy -- Part II. Technologies of support for decision making in modern business systems -- Chapter 6. The role and functions of mediator in the process of decision making in modern business systems / Aleksei V. Bogoviz, Svetlana V. Lobova, Yulia V. Ragulina, Alexander N. Alekseev and Karine S. Khachaturyan -- Chapter 7. Innovational managerial technologies of decision making in the sphere of digital medicine in modern business system / Sergey V. Shkodinsky, Elena A. Kondratyeva, Igor V. Bulava, Igor V. Chistov and Sergey E. Zakutnev -- Chapter 8. Innovative management technologies of decision-making in modern business systems / Natalia A. Shchukina and Irina A. Tarasova -- Chapter 9. Analysis and support of decision making with the use of latest information and communication technologies for development of social and economic area with regard to capabilities of different categories of population / M.A. Timoshenko, Aleksey F. Rogachev, L.N. Medvedeva and Kirill E. Tokarev -- Chapter 10. Intellectual support for decisions in modern business systems / Irina V. Gashenko, Elena N. Makarenko, Yuliya S. Zima and Tatyana V. Makarenko -- Part III. Recommendations for improving the process of decision making in modern business systems -- Chapter 11. Perspective directions of improving the process of decision making in business systems by the example of modern Russia / Olga G. Semenyuta, Irina V. Orobinskaya, Neonila M. Shiryaeva and Yuliya A. Kruchanova -- Chapter 12. The mechanism of highly-effective decision making in modern business systems / Larisa A. Ilyina, Vladimir S. Tikhonov, Yuliya S. Sakhno and Natalia V. Viktorova -- Chapter 13. Strategy of highly-efficient decision making in modern business systems / Ekaterina S. Kovanova, Angelina E. Kolieva, Raphael F. Mustafin and Zalina B. Tedeeva -- Chapter 14. The optimization model of decision making in modern business systems / Irina A. Tarasova, Natalia A. Shchukina, Oksana A. Avdeyuk and Vera V. Nekrasova -- Chapter 15. Algorithm of implementation of the optimization model of decision making in modern business systems / Nataliya V. Asanova, Tatyana E. Kozhanova, Yuliya Y. Andreeva and Vera V. Nekrasova -- Chapter 16. Development of tools to support decision making in evaluating the performance of state energy efficiency policy (the case of Russian regions) / Lyudmila Y. Bogachkova , Lidiya S. Guryanova and Shamam G. Khurshudyan -- Chapter 17. Structuring the information base on production losses in the conditions of effective production management / Viktor P. Kuznetsov, Igor E. Mizikovsky, Ekaterina P. Garina, Elena V. Romanovskaya and Nataliya S. Andryashina -- Conclusions -- Index.
Includes index.
Print version record.
Keywords: Decision making; Management information systems; Business & Economics -- Decision-Making & Problem Solving; Management decision making